Discourse Moves and Emotion in Knowledge Building Discourse and Metadiscourse - Zhu, Gaoxia; Scardamalia, Marlene; Moreno, Matthew; Martins, Michael; Nazeem, Raadiyah; Lai, Zhixin (Frontiers in Education, 2022)
Individuals' emotional and cognitive characteristics are interrelated. Metadiscourse, discourse about discourse which is emphasized in Knowledge Building (KB), has the potential to influence students' emotions because it enables them to identify the ideas and questions that they are passionate about and take more control of learning. To examine how students' discourse moves emotions differ in discourse and metadiscourse sessions, we considered the discourse move and emotion reflected in each student utterance as a state and uncovered how they unfold in KB discourse and metadiscourse sessions in terms of frequency, transition, and spread. Grades 2 and 3 students' utterances were analyzed. We found that discourse move-emotion states such as "reflection and positive" and "proposing new directions for inquiry and curiosity" were among the most occurring states in the metadiscourse sessions, but not in the discourse sessions. The transition rates indicate that a student's reflection tended to trigger more reflection; proposing new directions for inquiry led to more proposing. The sequential pattern analysis suggests some sub-sequences were specific to metadiscourse sessions. This study implies that engaging in metadiscourse contributes to students' productive KB and positive emotions.